2012
DOI: 10.1111/j.1471-0307.2012.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of time elapsed after milking and lactation stage on the lactoperoxidase system of milk in Sahiwal cattle and Nili‐Ravi buffaloes

Abstract: The effects of time elapsed after milking and lactation stage were assessed on the lactoperoxidase (LP) enzyme activity and concentrations of thiocyanate in Sahiwal cattle (N = 15) and Nili‐Ravi buffaloes (N = 15). The LP activity and thiocyanate concentrations decreased as the time elapsed after milking (P < 0.05) but the concentration of these components increased as the lactation advanced. The LP enzyme activity was sufficient until 12 h post milking but the thiocyanate concentration after 8 h decreased to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…The thiocyanate levels obtained in this study were higher than those found by Fweja et al (2007) in milk of Ayrshire and Tanzania Short Horn Zebu cows, and by Ponce (2012) in animals of a rustic breed in Cuba, Venezuela, and Mexico. The thiocyanate levels also varied between the groups, corroborating the results found by Ponce et al (1998), Fonteh et al (2002), Seifu et al (2007), and Yaqub et al (2012).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The thiocyanate levels obtained in this study were higher than those found by Fweja et al (2007) in milk of Ayrshire and Tanzania Short Horn Zebu cows, and by Ponce (2012) in animals of a rustic breed in Cuba, Venezuela, and Mexico. The thiocyanate levels also varied between the groups, corroborating the results found by Ponce et al (1998), Fonteh et al (2002), Seifu et al (2007), and Yaqub et al (2012).…”
Section: Resultssupporting
confidence: 88%
“…The mean activity of the lactoperoxidase found in this study was higher than those observed in studies carried out with Holstein cows in Iran (Asadpour et al, 2008) and in Italy (Calamari et al, 2005). The lactoperoxidase activity had a high variation when comparing the samples, corroborating the results found by Seifu et al (2007), Lujerdean and Buena (2010), and Yaqub et al (2012).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations